Real-time Ethernet In-Car Backbones: First Insights into an Automotive Prototype - Till Steinbach and Kai Müller and Franz Korf and René Röllig (Piscataway, New Jersey ; IEEE Press, 2014)
The communication infrastructure of today's automobiles forms a complex composition of heterogeneously interconnected components. At the same time, demands for higher bandwidth and low-latency communication are emerging from chassis control, camera based driver assistance and infotainment that cannot be accommodated by established technologies. A new approach towards a flexible highly scalable network is real-time Ethernet. The RECBAR research project develops and evaluates concepts and technologies for next-generation in-car backbones. In this demo we show a prototype based on a 2014 Volkswagen Golf 7 series car additionally equipped with high-bandwidth sensors, such as HD cameras and 3D laser scanners. The car uses a backbone network utilising time-triggered real-time Ethernet for the deterministic transmission of messages with hard real-time as well as rate-limiting and best-effort frames for messages with relaxed timing requirements. On the physical layer the setup utilises the OPEN Alliance 100Mbit/s BroadR-Reach (OABR or 100 BASE-T1) in addition to 100 BASE-TX.